Hervormde Barthiaanse Skrifbeskouing - Malan, Gert J. (HTS teologiese studies, 2017)
This article constitutes a summary of the development of a unique Barthian blend of Reformed Scripture view by theologians of the faculty of the Netherdutch (Hervormde) Church of Africa. The influence of Barth’s Scripture view is discussed according to central themes which were further developed, namely Word of God, revelation, faith, inspiration, authority of Scripture and the relation of the Old to the New Testament, and how these developed. The article concludes that the ‘Hervormde’ blend of Barthian view of Scripture is a gem to be treasured and guarded against un-Reformed authoritarian fundamentalism and foundationalism.